2010
DOI: 10.1521/soco.2010.28.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Loss Aversion and Status Quo Label Bias

Abstract: Many factors contribute to status quo perseverance, some justifiable, some not. We focus on an advantage accruing to a policy from just calling it status quo, which is that the mere label makes it look better. When comparing pros and cons of competing policies, labeling one "status quo" sets it up as the reference point with respect to which pros and cons are potentially either losses or gains. Since "losses loom larger than gains", pros one has weigh more than pros one does not, while the reverse holds for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…They also give more weight to potential losses than to equal gains (they are "loss averse," Tversky & Kahneman, 1991). Because the status quo operates as a reference point from which change is considered, the costs of change should carry more weight than potential benefits, creating a relative advantage for the existing state of affairs (Moshinsky & Bar-Hillel, 2010). This aversion to risk and loss leads to greater regret for action than for inaction (Kahneman & Tversky, 1982), and more regret is experienced when a decision changes the status quo than when it maintains it (Hesketh, 1996;Ritov & Baron, 1992;cf.…”
Section: Processes Related To Change Resistancementioning
confidence: 99%
“…They also give more weight to potential losses than to equal gains (they are "loss averse," Tversky & Kahneman, 1991). Because the status quo operates as a reference point from which change is considered, the costs of change should carry more weight than potential benefits, creating a relative advantage for the existing state of affairs (Moshinsky & Bar-Hillel, 2010). This aversion to risk and loss leads to greater regret for action than for inaction (Kahneman & Tversky, 1982), and more regret is experienced when a decision changes the status quo than when it maintains it (Hesketh, 1996;Ritov & Baron, 1992;cf.…”
Section: Processes Related To Change Resistancementioning
confidence: 99%
“…However, a robust literature in social psychology and behavioral economics has found that a variety of subtle changes to menu design can affect choices, even when the set of options is unrestricted and there are no search costs. 5 For instance, merely labeling a policy option as the status quo generally increases its support, 6,7 and the first option on a menu or ballot draws an excess share of choices. 8,9 Thus, failure to consider the behavioral implications of EHR menu design may unintentionally bias provider decisions and undermine patient health.…”
Section: Introductionmentioning
confidence: 99%
“…When a reference point is dominated by both alternatives (Group 1), the CLA, SQB and GSQB models predict no preference reversal -the decision maker should stick with her earlier choice. 29 Therefore, comparing the choice behavior of agents when there is no reference point and when there is one (r 5 , r 6 , or r 7 ) provides a very though test for the CLA, SQB and GSQB models. On the other hand, the other models do not make any particular predictions in this type of switches.…”
mentioning
confidence: 99%
“…The LA model predicts at least as many preference reversals at r 4 as at r 3 . 29 We assume agents are not indifferent between any two consumption bundles. Of course, allowing for indifference improves the explanatory power of the CLA, SQB and GSQB models.…”
mentioning
confidence: 99%